2019
DOI: 10.1029/2017tc004932
|View full text |Cite
|
Sign up to set email alerts
|

The Culmination of an Oblique Time‐Transgressive Arc Continent Collision: The Pollino Massif Between Calabria and the Southern Apennines, Italy

Abstract: The Pollino Massif is the most southeastern outcrop of the Apennine core. It marks the transition between Apenninic shortening and extension, respectively, SE and NW of the massif and is also the cusp of a southeastward plunge that characterizes the submerged Apennines. The SE limit of NE‐SW extension merges with the east limit of Tyrrhenian extension in Calabria. This strategic position is expected to transition southeastward in the progressive oblique collision of the Calabrian forearc and Apulia. We test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 73 publications
(175 reference statements)
0
14
2
Order By: Relevance
“…From the geological point of view, this result is not surprising, relying on the fact that Southern Italy is floored by the fold and thrust belt in the western and central part (Ferranti et al, 2017). More specifically, regarding the Pollino area, it has been found that during the late contraction stage (Late Pliocene to Early Pleistocene), the thick Apulia crust was involved in the thrust system and then reversely reactivated as normal faults in the actual extensional regime, responsible for the seismic hazard of the area (Ferranti et al, 2017;Filice and Seeber, 2019). For the first time, a three-dimensional tomographic image shows with impressive detail what until now had been hypothesized by geological sections.…”
Section: Discussionmentioning
confidence: 86%
“…From the geological point of view, this result is not surprising, relying on the fact that Southern Italy is floored by the fold and thrust belt in the western and central part (Ferranti et al, 2017). More specifically, regarding the Pollino area, it has been found that during the late contraction stage (Late Pliocene to Early Pleistocene), the thick Apulia crust was involved in the thrust system and then reversely reactivated as normal faults in the actual extensional regime, responsible for the seismic hazard of the area (Ferranti et al, 2017;Filice and Seeber, 2019). For the first time, a three-dimensional tomographic image shows with impressive detail what until now had been hypothesized by geological sections.…”
Section: Discussionmentioning
confidence: 86%
“…The Crati Basin hosts well‐known examples of fault‐controlled shoal‐water and Gilbert‐type deltas (Colella, 1988b), and in the present study we focus on facies variations and vertical evolution of the lower portion of the Early‐Middle Pleistocene Civita section (Figure 4a). The Civita section developed in the northern sector of the Crati Basin along a fault‐segment of the 15‐km long Pollino Fault (Colella, 1988a,b; Filice and Seeber, 2019), and pertain to the Pleistocene Synthem (PlS) defined by Spina, Tondi, and Mazzoli (2011; Figure 4a). The Pollino Fault has an oblique normal‐sinistral kinematics (Chiarabba, Agostinetti, & Bianchi, 2016; Ghisetti & Vezzani, 1982; Monaco & Tansi, 1992; Tansi et al., 2007, 2016; Van Dijk et al., 2000) forming a SW facing fault scarp that favoured the formation of several vertically stacked Plio–Pleistocene deltaic units having a total thickness of ~300 m (Colella, 1988b; Figure 4a).…”
Section: Geological Settingmentioning
confidence: 99%
“…This set of conjugate SW-and NEdipping normal faults represents the local expression of the Quaternary extensional belt that develops all along the Ital-ian peninsula, nearly parallel to the axial zone of the Apennines, from northern Tuscany to the Calabrian Arc (Brozzetti, 2011). North of Campotenese (Lucania and southern Campania), the Apennine extensional belt includes several continental basins and their boundary faults, such as the Irpinia, Vallo di Diano, Tanagro, Melandro-Pergola, and Val d'Agri (Ascione et al, 1992;Maschio et al, 2005;Amicucci et al, 2008;Villani and Pierdominici, 2010;Brozzetti, 2011;Filice and Seeber, 2019;Bello et al, 2021). To the south, it continues with the Crati graben that dissects the northern sector of the Calabrian Arc (Tortorici et al, 1995;Brozzetti et al, 2012Brozzetti et al, , 2017b.…”
Section: Tectonic Setting and Seismicitymentioning
confidence: 99%